2021
DOI: 10.3390/metabo11050331
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Thinning and Vineyard Site Modulate the Metabolomic Profile of Ribolla Gialla Base and Sparkling Wines

Abstract: Depending on the vineyard location, cluster thinning (CT) may represent an effective tool to obtain the desired grape composition and wine quality. The effect of 20% cluster thinning on Ribolla Gialla (Vitis vinifera L.) sparkling wine aroma, lipid compounds, and aromatic amino acid (AAA) metabolites composition was studied for three consecutive seasons in two vineyards located in the Friuli Venezia Giulia region, Italy. In the examined sparkling wines, the vintage meteorological conditions exhibited significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 85 publications
(73 reference statements)
0
8
1
Order By: Relevance
“…Cluster thinning had a certain positive impact on few VOCs, increasing 1‐butanol (fruity flavor), 1‐hexanol (green note), benzyl alcohol and 2‐phenylethanol (fruity and rose nuance), and benzaldehyde (fruity odor and flavor). Also Škrab et al 34 . recently showed that the thinning treatment in Ribolla Gialla grapes significantly influenced only a very scarce number of individual aroma compounds in wines, especially alcohols, leaving esters, aldehydes, and ketones unaffected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster thinning had a certain positive impact on few VOCs, increasing 1‐butanol (fruity flavor), 1‐hexanol (green note), benzyl alcohol and 2‐phenylethanol (fruity and rose nuance), and benzaldehyde (fruity odor and flavor). Also Škrab et al 34 . recently showed that the thinning treatment in Ribolla Gialla grapes significantly influenced only a very scarce number of individual aroma compounds in wines, especially alcohols, leaving esters, aldehydes, and ketones unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although this agronomic practice is widely used to regulate the source/sink ratio and thus increase the accumulation of the secondary metabolites, there are contrasting results in the literature about the effect of cluster removal on the aroma composition of wines. 29 Some studies reported the enhancement of monoterpenes and esters after cluster thinning on red grapevines, such as Syrah, Pinot noir, and Tempranillo, [30][31][32] whereas other studies noted that the crop level had little impact on the volatile profile of wines, [33][34][35] depending on the grape variety and vineyard location.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of volatile compounds in wort at the end of fermentation were conducted as previously described (Škrab et al, 2021) with the following modifications. Briefly, 0.5 ml of the samples in 20 ml vials were supplemented with sodium chloride to a final concentration of 1 g mL −1 and 25 μl of the 2‐octanol as the internal standard (final concentration 200 μg L −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A similar result was obtained for the C13-norisoprenoid group of substances. In addition, the effect of cluster thinning produced the increase in metabolites associated with aromatic amino acids [153].…”
Section: Cluster Thinningmentioning
confidence: 99%